On the condition of anonymity : unnamed sources and the battle for journalism - Carlson, Matt, 1977- (History of communication., 2011)
Matt Carlson confronts the promise and perils of unnamed sources in this exhaustive analysis of controversial episodes in American journalism during the George W. Bush administration, from prewar reporting mistakes at the New York Times and Washington Post to Judith Miller's involvement in the Valerie Plame leak case and Dan Rather's lawsuit against CBS News. Weaving a narrative thread that stretches from the uncritical post-9/11 era to the unmasking of Deep Throat and the spectacle of the Scooter Libby trial, Carlson examines a tense period in American history through the lens of journalism. Revealing new insights about high-profile cases involving confidential sources, he highlights contextual and structural features of the era, including pressure from the right, scrutiny from new media and citizen journalists, and the struggles of traditional media to survive amid increased competition and decreased resources. In exploring the recent debates among journalists and critics over the appropriate roles of media, Carlson underscores the potential for unattributed information to be both an effective tool in uncovering necessary information about vital institutions and a means for embroiling journalists in controversy and damaging the credibility of already struggling news outlets. -- from Book Jacket.